BoneBridge implantation in patients with single-sided deafness resulting from vestibular schwannoma resection: objective and subjective benefit evaluations. (3rd October 2018) - Yang, Jie; Wang, Zhaoyan; Huang, Meiping; Chai, Yongchuan; Jia, Huan; Wu, Yingwei; Dai, Yongming; Li, Yun; Wu, Hao
Abstract: Background: The BoneBridge could rehabilitate hearing for patients with single-sided deafness (SSD). Objectives: To evaluate the objective and subjective benefits of BoneBridge implantation in patients after vestibular Schwannoma resection and to explore the factors affecting the benefits. Material and methods: We prospectively enrolled all 15 patients implanted with BoneBridge after VS resection from January to June 2017. The primary outcome was the ability to hear in noisy conditions. The secondary outcomes were the soft-band BoneBridge try-on rate, the frequency of BB use, the sound source localization test result, and questionnaire measures of quality of life (QoL). Results: Patients showed better speech recognition ability in the presence of noise with the BoneBridge. The BoneBridge provided no help in sound localization, although most patients reported subjective sound localization benefits. The results of QoL questionnaires showed significant satisfaction with BoneBridge implantation. The unilateral hearing deprivation duration and high education levels had significant impacts on the subjective benefits of patients. Conclusions: The BoneBridge could improve speech recognition performance in complex auditory backgrounds, as well as QoL, especially in patients with short unilateral hearing deprivation durations and high education levels. Significance: The BoneBridge is an effective hearing aid for single-sided deafness patients after VS removal.